2003
DOI: 10.1113/jphysiol.2002.036129
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Regulation of Ca2+ Release in Permeabilized Mammalian Skeletal Muscle Fibres

Abstract: In the present study, the link between cellular metabolism and Ca2+ signalling was investigated in permeabilized mammalian skeletal muscle. Spontaneous events of Ca2+ release from the sarcoplasmic reticulum were detected with fluo‐3 and confocal scanning microscopy. Mitochondrial functions were monitored by measuring local changes in mitochondrial membrane potential (with the potential‐sensitive dye tetramethylrhodamine ethyl ester) and in mitochondrial [Ca2+] (with the Ca2+ indicator mag‐rhod‐2). Digital fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
150
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(158 citation statements)
references
References 47 publications
7
150
0
1
Order By: Relevance
“…In humans exercising for 1 h, the amount of Ca 2ϩ in the mitochondria only increased by ϳ50% above the level in rested muscle (297). It should also be noted that the experiments in mammalian fibers reporting specific tunneling of SR Ca 2ϩ to the mitochondria (223,401) were performed with skinned fibers under conditions where the SR would have been loaded at near-maximal capacity, and this likely increased the extent of Ca 2ϩ uptake by the mitochondria. In summary, the mitochondria appear to play at most a minor role in directly influencing overall Ca 2ϩ movements during EC coupling.…”
Section: Mitochondrial Ca 2؉ Handlingmentioning
confidence: 98%
See 1 more Smart Citation
“…In humans exercising for 1 h, the amount of Ca 2ϩ in the mitochondria only increased by ϳ50% above the level in rested muscle (297). It should also be noted that the experiments in mammalian fibers reporting specific tunneling of SR Ca 2ϩ to the mitochondria (223,401) were performed with skinned fibers under conditions where the SR would have been loaded at near-maximal capacity, and this likely increased the extent of Ca 2ϩ uptake by the mitochondria. In summary, the mitochondria appear to play at most a minor role in directly influencing overall Ca 2ϩ movements during EC coupling.…”
Section: Mitochondrial Ca 2؉ Handlingmentioning
confidence: 98%
“…Such Ca 2ϩ uptake may stimulate mitochondrial ATP production, although it may not be essential (68). It has been frequently suggested that Ca 2ϩ uptake by the mitochondria may play a significant role in overall Ca 2ϩ movements in a fiber, particularly those mitochondria situated close to the SR (223,401), with the effect possibly being more important in frog fibers than in mammalian fibers (68,270). However, the mitochondria do not contain high-capacity Ca 2ϩ binding proteins such as calsequestrin, and the absolute amount of Ca 2ϩ contained within the mitochondria in frog fibers at rest, or after stimulation by either a single tetanus or to fatigue, is Ͻ2% of that contained within the SR (190,408).…”
Section: Mitochondrial Ca 2؉ Handlingmentioning
confidence: 99%
“…Indeed, the SACs blockade induced by using streptomycin has been shown to reduce intracellular calcium levels in mdx mice [86,88]. Moreover, it has been reported that membrane stressors, such as isometric and eccentric contraction, induce increased ROS production in mdx mice, leading to Ca 2+ signaling dysfunction through the oxidation of Ca 2+ channels [89,90]. Elevated intracellular concentration of Ca 2+ can alter mitochondria permeability and function, thereby inducing degenerative pathways and ROS production [86,[91][92][93][94].…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Adult mammalian skeletal muscle fibers usually do not show spontaneous Ca 2ϩ sparks (29,232), except when the sarcolemma is permeabilized, (36,126,282) or in certain pathological states, e.g., mitochondrial degradation or osmotic shock (108,109,269), nor do they show sparks in response to depolarization (36,232). Because sparks have been recorded in myotubes expressing either RyR1 or RyR3 alone (28,29,270), it is certain that both RyR1 and RyR3 can produce Ca 2ϩ sparks.…”
Section: Ca 2ϩ Sparks and Ryr3mentioning
confidence: 99%